Cross-linked hyaluronic acid or salt thereof as well as preparation method and application of cross-linked hyaluronic acid or salt thereof
By performing complex cross-linking of high and low molecular weight hyaluronic acid under the condition of large alkaline solution, a three-dimensional loose network structure is formed, and further cross-linking is carried out under the condition of small alkaline solution, the existing technology is solved The problems of crosslinking agent residue and insufficient gel performance have achieved efficient preparation of hyaluronic acid gels, with good water absorption and mechanical properties.
Patent Information
- Application Number
- CN202310794020.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot take into account the industrial needs of the simplicity, safety, effective removal of crosslinking agents, strong viscosity, high cohesion and low water absorption of the crosslinking hyaluronic acid gel preparation process.
By combining high and low molecular weight hyaluronic acid or its salt, crosslinking is performed under the condition of a large amount of alkaline solution to form a three-dimensional loose network structure, and then further crosslinking is performed under the condition of a small amount of alkaline solution. The crosslinking agent that has not been fully reacted is consumed to form a soft elastic chimeric structure with loose pores wrapped around elastic hard balls.
It achieves good support, ductility and deformation resistance of the gel, and improves water absorption and water retention, has better tissue compatibility, and is suitable for flat injection filling on the inner and outer surfaces of the cavity.
Smart Images

Figure CN119219991A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and specifically relates to a cross-linked hyaluronic acid or a salt thereof, and a preparation method and application thereof. Background Art
[0002] Hyaluronic acid is a natural mucopolysaccharide, composed of (1-β-4) D-glucuronic acid and (1-β-3) N-acetyl-D-aminoglucose disaccharide units repeatedly connected. It is an important component of human and animal skin, vitreous body, joint lubricating fluid and cartilage tissue. Sodium hyaluronate has multiple functions in the human body, including: space filling, hydration, joint lubrication, and providing a matrix through which cells can migrate. Although hyaluronic acid has many advantages, the weak mechanical properties of natural hyaluronic acid and its easy degradation in the body limit its application in biomaterials. Cross-linked sodium hyaluronate is a polymer gel obtained by chemical cross-linking of sodium hyaluronate, which makes up for the short retention time of natural sodium hyaluronate.
[0003] Patent document CN106279726B discloses a cross-linked sodium hyaluronate gel and a preparation method thereof. Under ultrasonic conditions, a cross-linking agent is added dropwise to an alkaline aqueous solution of sodium hyaluronate to carry out a cross-linking reaction. After the reaction is completed, the pH value of the system is adjusted to 7.1-7.5 with an acid, stirred for 1-2 hours, and then precipitated with anhydrous ethanol to obtain a cross-linked sodium hyaluronate gel. However, this method does not have a step of removing the cross-linking agent, which easily causes the cross-linking agent to remain.
[0004] Patent document CN112940300B discloses a method for preparing a cross-linked hyaluronic acid gel, comprising the following steps:
[0005] (1) Mixing an aqueous solution containing a crosslinking agent and hyaluronic acid, a metal salt thereof, or a mixture thereof in a non-neutral environment to form a mixed solution; (2) placing the mixed solution at a temperature lower than 0°C and higher than the eutectic point of the mixed solution and maintaining the temperature for a time sufficient to form a solid-liquid heterogeneous system; (3) placing the heterogeneous system at a temperature lower than 0°C and higher than the eutectic point of the mixed solution to perform a crosslinking reaction; (4) melting the solid phase in the heterogeneous system after the crosslinking reaction, and optionally neutralizing, purifying, and homogenizing. However, the neutralization step described in this method cannot ensure that the pH of the system decreases more gently, thereby easily destroying the three-dimensional crosslinked structure of the sodium hyaluronate gel system.
[0006] In summary, the existing technology cannot take into account the industrialization requirements of hyaluronic acid gel, such as simple preparation process, good safety, effective removal of cross-linking agents, strong viscosity, high cohesion, and low water absorption. Summary of the invention
[0007] The present invention overcomes the defects in the prior art and provides a cross-linked hyaluronic acid or its salt composition and a preparation method and application thereof.
[0008] The first aspect of the present invention provides a cross-linked hyaluronic acid or a salt thereof, wherein the preparation method of the cross-linked hyaluronic acid or a salt thereof comprises the following steps:
[0009] (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt;
[0010] (2) mixing hyaluronic acid III or its salt, a second alkaline solution and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt;
[0011] (3) After diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, add the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mix and react to obtain the cross-linked hyaluronic acid or its salt.
[0012] Furthermore, the mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution.
[0013] Furthermore, the molecular weight of the hyaluronic acid I is higher than the molecular weights of the hyaluronic acids II, III and IV.
[0014] Further, the concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL (e.g., 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 36 mg / mL, 37 mg / mL, 38 mg / mL, 39 mg / mL, 40 mg / mL, 41 mg / mL, 42 mg / mL, 43 mg / mL, 44 mg / mL, 45 mg / mL, 46 mg / mL, 47 mg / mL, 48 mg / mL, 49 mg / mL, 50 mg / mL, 51 mg / mL, 52 mg / mL, 53 mg / mL, 54 mg / mL, 55 mg / mL, 56 mg / mL, 57 mg / mL, 58 mg / mL, 59 mg / mL, 60 mg / mL, 61 mg / mL, 62 mg / mL, 63 mg / mL, 64 mg / mL, 65 mg / mL, 66 mg / mL, 67 mg / mL, 68 mg / mL, 69 mg / mL, 70 mg / mL, 71 mg / mL, 72 mg / mL, 73 mg / mL, 74 mg / mL 7mg / mL, 48mg / mL, 49mg / mL, 50mg / mL, 51mg / mL, 52mg / mL, 53mg / mL, 54mg / mL, 55mg / mL, 56mg / mL, 57mg / mL , 58 mg / mL, 59 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL), preferably 12 to 90 mg / mL, more preferably 15 to 80 mg / mL.
[0015] Further, in step (2), the concentration of the second alkaline solution is 0.1-50 mg / mL (such as 0.1 mg / mL, 1 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL, 18 mg / mL, 19 mg / mL, 20 mg / mL, 21 mg / mL, 22 mg / mL, 23 mg / mL, 24 mg / mL, 25 mg / mL, 26 mg / mL, 27 mg / mL, 28 mg / mL, 29 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL), preferably 1-40 mg / mL, and more preferably 5-30 mg / mL.
[0016] Furthermore, the molecular weight of the hyaluronic acid I is 900-3000 kDa (such as 900 kDa, 950 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa, 2000 kDa, 2500 kDa, 3000 kDa), preferably 1000-2000 kDa, and more preferably 1200-1600 kDa.
[0017] In one embodiment of the present invention, the molecular weight of the hyaluronic acid I is 1500 kDa.
[0018] Further, the molecular weight of the hyaluronic acid II, III, and IV is 100 to 1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300 to 800 kDa, and more preferably 400 to 700 kDa.
[0019] Furthermore, the molecular weights of the hyaluronic acids II, III and IV may be the same or different.
[0020] In one embodiment of the present invention, the molecular weight of hyaluronic acid II, III, and IV is 600 kDa.
[0021] Furthermore, in step (1), the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt is 2-10:1, preferably 3-9:1.
[0022] In one embodiment of the present invention, the mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 3:1.
[0023] Furthermore, the mass ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1; preferably 2-6:1.
[0024] Furthermore, the amount of hyaluronic acid IV or its salt added is 5-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.
[0025] Furthermore, water is added in step (3) to dilute the alkaline solution to a concentration equal to the concentration of the second alkaline solution in step (2).
[0026] Furthermore, the reaction temperature in steps (1), (2) and (3) is 20 to 30°C.
[0027] Furthermore, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.
[0028] Furthermore, the reaction temperature and time in steps (1), (2) and (3) may be the same or different.
[0029] In one embodiment of the present invention, the reaction temperature in step (1) is 25° C. and the reaction time is 20 h.
[0030] Furthermore, the hyaluronic acid I or its salt, hyaluronic acid II or its salt, hyaluronic acid III or its salt and hyaluronic acid IV or its salt can be derived from animals or obtained through bacterial fermentation.
[0031] Further, the hyaluronate is selected from any one of sodium hyaluronate (HA), potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate; preferably sodium hyaluronate.
[0032] Further, the cross-linked hyaluronate is selected from any one of cross-linked sodium hyaluronate, cross-linked potassium hyaluronate, cross-linked calcium hyaluronate, cross-linked magnesium hyaluronate, cross-linked ammonium hyaluronate, cross-linked tetrabutylammonium hyaluronate, cross-linked bismuth hyaluronate and zinc hyaluronate, preferably cross-linked sodium hyaluronate.
[0033] Furthermore, the alkaline solution is selected from: a solution prepared by one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, and potassium sulfite, preferably a sodium hydroxide solution. The first alkaline solution and the second alkaline solution may be the same or different; preferably, the first alkaline solution and the second alkaline solution are the same.
[0034] Furthermore, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether (BDDE), divinyl sulfone, polyethylene glycol, genipin and carbodiimide, preferably 1,4-butanediol diglycidyl ether.
[0035] Furthermore, the cross-linking degree of the obtained cross-linked hyaluronic acid or its salt is 1% to 6%, preferably 1.5% to 5%.
[0036] The present invention firstly carries out compounding of high and low molecular weight hyaluronic acid or its salt, under the condition that the amount of alkaline solution is large, by destroying the hydrogen bonding between hyaluronic acid or its salt, the molecular chain of hyaluronic acid or its salt is fully extended and stretched, wherein the molecular chain of low molecular weight hyaluronic acid or its salt can freely carry out irregular translation or rotational motion while stretching, so that low molecular weight hyaluronic acid or its salt can be interspersed or erected between high molecular weight hyaluronic acid or its salt, realize high and low molecular weight hyaluronic acid or its salt interspersed crosslinking;Meanwhile, the amount of alkaline solution is large, and there is certain degradation effect on the molecular chain of hyaluronic acid or its salt while crosslinking, and finally forms a three-dimensional loose network structure with large mesh spacing. Subsequently, under the condition that the amount of alkaline solution is small, low molecular weight hyaluronic acid or its salt is crosslinked, the amount of alkali solution is low, the hydrogen bonding between hyaluronic acid or its salt is strong, and the molecular chain winding is relatively common, and hyaluronic acid or its salt and crosslinking agent are easy to react quickly to form a compact network structure, and obtain micron gel particles. However, due to the fact that the cross-linking reaction is not thorough enough under the condition of a large amount of alkaline solution, a part of the cross-linking agent still exists. By adding water to adjust the dilution, the condition of a large amount of alkaline solution is changed to a condition of a small amount of alkaline solution, and micron gel particles, hyaluronic acid or its salt are added to continue the reaction and consume the cross-linking agent that has not reacted completely, so that the compact structure can penetrate into the looser structure, forming a cross-linked hyaluronic acid or its salt gel with a soft elastic mosaic structure of loose pores encapsulating elastic hard balls. Since the loose pore area has good ductility, the gel has good support performance, ductility and deformation resistance, and has better water absorption and water retention, better tissue compatibility, and is more suitable for flat injection filling of the inner and outer surfaces of the cavity.
[0037] The second aspect of the present invention provides a cross-linked hyaluronic acid or salt composition, which comprises: the cross-linked hyaluronic acid or salt thereof of the first aspect, non-cross-linked hyaluronic acid or salt thereof, phosphate buffer, local anesthetic and water-soluble cellulose.
[0038] Further, the mass concentration of the cross-linked hyaluronic acid or its salt is 1-30 mg / ml (such as 1 mg / ml, 2 mg / ml, 3 mg / ml, 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml, 10.5 mg / ml, 11 mg / ml, 11.5 mg / ml, 12 mg / ml, 12.5 mg / ml, 13 mg / ml, 13.5 mg / ml, 14 mg / ml, 14.5 mg / ml, 15 mg / ml, 15.5 mg / ml, 16 mg / ml, 16.5 mg / ml, 17 mg / ml, 17.5 mg / ml, 18 mg / ml, 18.5 mg / ml, 19 mg / ml, 19.5 mg / ml, 20 mg / ml), preferably 5-25 mg / ml, more preferably 10-20 mg / ml.
[0039] Further, the cross-linked hyaluronate is selected from any one of cross-linked sodium hyaluronate, cross-linked potassium hyaluronate, cross-linked calcium hyaluronate, cross-linked magnesium hyaluronate, cross-linked ammonium hyaluronate, cross-linked tetrabutylammonium hyaluronate, cross-linked bismuth hyaluronate and zinc hyaluronate, preferably cross-linked sodium hyaluronate.
[0040] Furthermore, the non-cross-linked hyaluronate is selected from any one of non-cross-linked sodium hyaluronate, non-cross-linked potassium hyaluronate, non-cross-linked calcium hyaluronate, non-cross-linked magnesium hyaluronate, non-cross-linked ammonium hyaluronate, non-cross-linked tetrabutylammonium hyaluronate, non-cross-linked bismuth hyaluronate and non-hyaluronate zinc, preferably non-cross-linked sodium hyaluronate.
[0041] Further, the concentration of the non-cross-linked hyaluronic acid or its salt is 0.2-10 mg / ml (such as 0.2 mg / ml, 0.3 mg / ml, 0.4 mg / ml, 0.5 mg / ml, 0.6 mg / ml, 0.7 mg / ml, 0.8 mg / ml, 0.9 mg / ml, 1 mg / ml, 1.1 mg / ml, 1.2 mg / ml, 1.3 mg / ml, 1.4 mg / ml, 1.5 mg / ml, 1.6 mg / ml, 1.7 mg / ml, 1.8 mg / ml, 1.9 mg / ml, 2 mg / ml, 2.5, 3 mg / ml, 3.5, 4 mg / ml, 4.5 mg / ml, 5 mg / ml, 5.5 mg / ml, 6 mg / ml, 6.5 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml), preferably 0.5-8 mg / ml, more preferably 1-6 mg / ml.
[0042] Further, the molecular weight of the non-cross-linked hyaluronic acid or its salt is 100-1000 kDa (such as 100 kDa, 150 kDa, 200 kDa, 250 kDa, 300 kDa, 350 kDa, 400 kDa, 450 kDa, 500 kDa, 550 kDa, 560 kDa, 570 kDa, 580 kDa, 590 kDa, 600 kDa, 610 kDa, 620 kDa, 630 kDa, 640 kDa, 650 kDa, 700 kDa, 750 kDa, 800 kDa, 850 kDa, 900 kDa, 1000 kDa), preferably 300-800 kDa, and more preferably 400-700 kDa.
[0043] Furthermore, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose, preferably hydroxypropyl methylcellulose.
[0044] Furthermore, the content of the water-soluble cellulose is in the range of 0.01 to 40 mg / ml, preferably 0.2 to 25 mg / ml, and more preferably 0.5 to 10 mg / ml.
[0045] Furthermore, the phosphate buffer comprises: disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride.
[0046] Further, the concentration of the disodium hydrogen phosphate is 0.01-10 mg / ml (e.g., 0.01 mg / ml, 0.02 mg / ml, 0.03 mg / ml, 0.04 mg / ml, 0.05 mg / ml, 0.06 mg / ml, 0.07 mg / ml, 0.08 mg / ml, 0.09 mg / ml, 1 mg / ml, 1.1 mg / ml, 1.2 mg / ml, 1.3 mg / ml, 1.4 mg / ml). , 1.5mg / ml, 1.6mg / ml, 1.7mg / ml, 1.8mg / ml, 1.9mg / ml, 2mg / ml, 3mg / ml, 4mg / ml, 5mg / ml, 6mg / ml, 7mg / ml, 8mg / ml, 9mg / ml, 10mg / ml), preferably, the concentration of disodium hydrogen phosphate is 3-10mg / ml, further preferably, the concentration of disodium hydrogen phosphate is 4-8mg / ml.
[0047] In one embodiment of the present invention, the concentration of disodium hydrogen phosphate is 10 mg / ml.
[0048] Further, the concentration of the sodium dihydrogen phosphate is 0.01-9 mg / ml (such as 0.01 mg / ml, 0.02 mg / ml, 0.03 mg / ml, 0.04 mg / ml, 0.05 mg / ml, 0.06 mg / ml, 0.07 mg / ml, 0.08 mg / ml, 0.09 mg / ml, 1 mg / ml, 1.5, 2 mg / ml, 2.5, 3 mg / ml, 3.5, 4 mg / ml, 4.5 mg / ml, 5 mg / ml, 5.5 mg / ml, 6 mg / ml, 6.5 mg / ml, 7 mg / ml, 7.5 mg / ml, 8 mg / ml, 8.5 mg / ml, 9 mg / ml), preferably, the concentration of the sodium dihydrogen phosphate is 1-7 mg / ml, further preferably, the concentration of the sodium dihydrogen phosphate is 2-6 mg / ml.
[0049] In one embodiment of the present invention, the concentration of sodium dihydrogen phosphate is 4 mg / ml.
[0050] Further, the concentration of potassium chloride is 0.01-7 mg / ml (such as 0.01 mg / ml, 0.02 mg / ml, 0.03 mg / ml, 0.04 mg / ml, 0.05 mg / ml, 0.06 mg / ml, 0.07 mg / ml, 0.08 mg / ml, 0.09 mg / ml, 1 mg / ml, 1.1 mg / ml, 1.2 mg / ml, 1.3 mg / ml, 1.4 mg / ml, 1.5 mg / ml). 1, 1.6 mg / ml, 1.7 mg / ml, 1.8 mg / ml, 1.9 mg / ml, 2 mg / ml, 2.5, 3 mg / ml, 3.5, 4 mg / ml, 4.5 mg / ml, 5 mg / ml, 5.5 mg / ml, 6 mg / ml, 6.5 mg / ml, 7 mg / ml), preferably, the concentration of potassium chloride is 0.05-5 mg / ml, more preferably, the concentration of potassium chloride is 0.1-3 mg / ml.
[0051] In one embodiment of the present invention, the concentration of potassium chloride is 1 mg / ml.
[0052] Furthermore, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof.
[0053] Further, the local anesthetic is selected from: lidocaine or its salt, bupivacaine or its salt, butancaine or its salt, carticaine or its salt, cinchocaine or its salt, chlorocaine or its salt, ethyl p-piperidylacetylaminobenzoate or its salt, etidocaine or its salt, mepivacaine or its salt, oxethicaine or its salt, prilocaine or its salt, ropivacaine or its salt, tolicaine or its salt, trimecaine or its salt, vardocaine or its salt, articaine or its salt, levobupivacaine or its salt, amicaine or its salt, cocaine or its salt, The group consisting of one or more of propancaine or its salt, chloroparacaine or its salt, cyclomethicaine or its salt, proparacaine or its salt, tetracaine or its salt, benzocaine or its salt, butacaine or its salt, butyrocaine or its salt, butylaminobenzoate or its salt, chloroprocaine or its salt, dimethocaine or its salt, oxybuprocaine or its salt, piperocaine or its salt, ethoxycaine or its salt, procaine or its salt, propoxycaine or its salt, tricaine or its salt, preferably lidocaine or its salt, more preferably lidocaine hydrochloride.
[0054] Further, the content range of the local anesthetic is 0.1-10 mg / ml (such as 0.1 mg / ml, 0.2 mg / ml, 0.5 mg / ml, 0.8 mg / ml, 1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml), preferably, the content range of the local anesthetic is 0.1-8 mg / ml, further preferably, the content range of the local anesthetic is 0.5-8 mg / ml, and even more preferably, the content range of the local anesthetic is 0.5-5 mg / ml.
[0055] In one embodiment of the present invention, the content of the local anesthetic is in the range of 3 mg / ml.
[0056] The present invention forms a gel composition by combining cross-linked hyaluronic acid or its salt gel with other auxiliary materials, so that the gel composition has better water absorption and water retention, better tissue compatibility, and is more suitable for flat laying and injection filling of the inner and outer surfaces of the cavity.
[0057] The third aspect of the present invention provides a method for preparing a cross-linked hyaluronic acid or salt composition thereof, comprising the following steps:
[0058] The cross-linked hyaluronic acid or its salt described in the first aspect is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is slowly adjusted to neutral with a lactic acid solution, and then a phosphate buffer, a local anesthetic, a water-soluble cellulose, and a non-cross-linked hyaluronic acid or its salt are added, mixed evenly, and sterilized by wet heat to obtain a composition.
[0059] Furthermore, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof.
[0060] Further, the local anesthetic is selected from: lidocaine or its salt, bupivacaine or its salt, butancaine or its salt, carticaine or its salt, cinchocaine or its salt, chlorocaine or its salt, ethyl p-piperidylacetylaminobenzoate or its salt, etidocaine or its salt, mepivacaine or its salt, oxethicaine or its salt, prilocaine or its salt, ropivacaine or its salt, tolicaine or its salt, trimecaine or its salt, vardocaine or its salt, articaine or its salt, levobupivacaine or its salt, amicaine or its salt, cocaine or its salt, The group consisting of one or more of propancaine or its salt, chloroparacaine or its salt, cyclomethicaine or its salt, proparacaine or its salt, tetracaine or its salt, benzocaine or its salt, butacaine or its salt, butyrocaine or its salt, butylaminobenzoate or its salt, chloroprocaine or its salt, dimethocaine or its salt, oxybuprocaine or its salt, piperocaine or its salt, ethoxycaine or its salt, procaine or its salt, propoxycaine or its salt, tricaine or its salt, preferably lidocaine or its salt, more preferably lidocaine hydrochloride.
[0061] Furthermore, the mass of the lidocaine hydrochloride is 0.1-1g (such as 0.1g, 0.2g, 0.3g, 0.35g, 0.4g, 0.45g, 0.5g, 0.6g, 0.7g, 0.8g, 0.9g, 1g).
[0062] Furthermore, the mass of the hydroxypropyl methylcellulose is 0.05-1g (such as 0.05g, 0.06g, 0.07g, 0.08g, 0.09g, 0.1g, 0.11g, 0.12g, 0.13g, 0.14g, 0.15g, 0.1g, 0.2g, 0.3g, 0.35g, 0.4g, 0.45g, 0.5g, 0.6g, 0.7g, 0.8g, 0.9g, 1g).
[0063] Furthermore, the non-cross-linked hyaluronic acid or its salt is 0.1-1g (such as 0.1g, 0.2g, 0.3g, 0.35g, 0.4g, 0.45g, 0.5g, 0.6g, 0.7g, 0.8g, 0.9g, 1g).
[0064] The fourth aspect of the present invention provides an application of the cross-linked hyaluronic acid or its salt described in the first aspect or the composition described in the second aspect, or the cross-linked hyaluronic acid or its salt composition prepared in the third aspect in the preparation of medicines, tissue engineering materials, and cosmetics.
[0065] Preferably, the tissue engineering material includes soft tissue filling material, cartilage repair material, and tissue engineering scaffold.
[0066] The fifth aspect of the present invention provides a non-medical cosmetic use of the cross-linked hyaluronic acid or its salt described in the first aspect or the composition described in the second aspect, or the cross-linked hyaluronic acid or its salt composition prepared in the third aspect, for improving the appearance of the skin, smoothing wrinkles, or repairing the appearance of the face or body of a subject.
[0067] Furthermore, the body appearance repair includes filling and repairing of moderate to severe labia majora atrophy or filling and repairing of the vaginal mucosal layer.
[0068] A sixth aspect of the present invention provides a non-medical method for improving the appearance of skin, smoothing wrinkles, or reshaping the face or body of a subject, comprising:
[0069] I) providing the cross-linked hyaluronic acid or its salt as described in the first aspect or the composition as described in the second aspect, or the cross-linked hyaluronic acid or its salt composition prepared in the third aspect, and
[0070] II) injecting the cross-linked hyaluronic acid or its salt as described in the first aspect or the composition as described in the second aspect, or the cross-linked hyaluronic acid or its salt composition prepared in the third aspect into the skin of a subject.
[0071] Furthermore, the composition of step II is injected into the dermis and / or subcutaneous tissue.
[0072] Beneficial effects of the present invention:
[0073] (1) The present invention firstly compounds high and low molecular weight hyaluronic acid or its salt, and under the condition of large amount of alkaline solution, by destroying the hydrogen bonding between hyaluronic acid or its salt, the molecular chain of hyaluronic acid or its salt is fully extended and stretched, and low molecular weight hyaluronic acid or its salt is interspersed or erected between high molecular weight hyaluronic acid or its salt while stretching, so as to realize the interspersed crosslinking of high and low molecular weight hyaluronic acid or its salt; at the same time, the amount of alkaline solution is large, and there is a certain degradation effect on the molecular chain of hyaluronic acid or its salt while crosslinking, and finally forms a three-dimensional loose network structure with large mesh spacing. Subsequently, under the condition of small amount of alkaline solution, low molecular weight hyaluronic acid or its salt is crosslinked, the amount of alkali solution is low, the hydrogen bonding between hyaluronic acid or its salt is strong, the molecular chain entanglement is relatively common, and hyaluronic acid or its salt and crosslinking agent are easy to react quickly to form a compact network structure, so as to obtain micron gel particles. However, due to the incomplete cross-linking reaction under the condition of large amount of alkali solution, a part of cross-linking agent still exists. By adding water to adjust the dilution, the condition of large amount of alkali solution is changed to that of small amount of alkali solution, and micron gel particles, hyaluronic acid or its salt are added to continue the reaction and consume the incompletely reacted cross-linking agent, so that the compact structure can penetrate into the looser structure to form a cross-linked hyaluronic acid or its salt gel with a soft elastic mosaic structure of loose pores wrapping elastic hard balls. Since the loose pore area has good ductility, the gel has good supporting performance, ductility and anti-deformation performance, and has better water absorption and water retention.
[0074] (2) The present invention can adjust the amount and molecular weight of high and low molecular weight hyaluronic acid or its salts according to the different implanted parts of the human body, so as to adjust the pore structure, water retention and mechanical properties of the cross-linked hyaluronic acid or its salts, thereby achieving precise matching of the gel filler with the injection site.
[0075] (3) The present invention forms a gel composition by combining cross-linked hyaluronic acid or its salt gel with auxiliary materials such as water-soluble cellulose, non-cross-linked hyaluronic acid or its salt, so that the gel composition has good water absorption and water retention properties, better tissue compatibility, and is more suitable for flat injection filling on the inner and outer surfaces of the cavity. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 The figure is a diagram of the water absorption effect of the gel composition samples (wherein, from left to right are Comparative Example 5, Comparative Example 3, Comparative Example 1, Example 3, Example 5, and Example 1).
[0077] Figure 2 The electron microscope scanning appearance morphology of the gel composition sample (wherein, a-Example 1, b-Example 3, c-Example 5, d-Comparative Example 1, e-Comparative Example 3, f-Comparative Example 5).
[0078] Figure 3It is the stress-strain scanning curve of the gel composition sample. DETAILED DESCRIPTION
[0079] In order to more clearly understand the technical content of the present invention, the following embodiments are given in detail, the purpose of which is only to better understand the content of the present invention but not to limit the protection scope of the present invention.
[0080] Example 1
[0081] (1) Preparation of cross-linked sodium hyaluronate I′: Take 1.5 g of 1500 kDa sodium hyaluronate raw material, take 0.5 g of 600 kDa sodium hyaluronate raw material, add 20 ml of water, add 5 ml of 250 mg / mL sodium hydroxide solution, add 0.06 ml of BDDE solution, mix well, react at 25° C. for 20 h, and obtain cross-linked sodium hyaluronate I′.
[0082] (2) Preparation of cross-linked sodium hyaluronate II′: Take 0.6 g of 600 kDa sodium hyaluronate raw material, add 6 ml of water, add 1.5 ml of 100 mg / mL sodium hydroxide solution to dissolve, add 0.03 ml of BDDE solution, mix well, react at 25°C for 20 hours, and make the gel into micron particles to obtain cross-linked sodium hyaluronate II′.
[0083] (3) Preparation of cross-linked sodium hyaluronate: Add 37.5 ml of water to the cross-linked sodium hyaluronate I′ of step (1), stir evenly, add the micronized particles of cross-linked sodium hyaluronate II′ of step (2) and 0.3 g of 600 kDa sodium hyaluronate raw material to the cross-linked sodium hyaluronate I′, mix evenly, and continue the reaction at 25° C. for 6 h. After the reaction is completed, cross-linked sodium hyaluronate is obtained.
[0084] (4) The cross-linked sodium hyaluronate obtained in step (3) is dialyzed and the pH value of the system is first adjusted to about 10-11 with a hydrochloric acid solution having a mass concentration of 8%, and then the pH value of the system is slowly adjusted to neutral with a 30% lactic acid solution. Subsequently, 100 ml of phosphate buffer (10 g of disodium hydrogen phosphate, 4 g of sodium dihydrogen phosphate, and 1 g of potassium chloride are weighed and dissolved in 1000 ml of water), 0.45 g of lidocaine hydrochloride, 0.15 g of hydroxypropyl methylcellulose, and 0.4 g of 600 kDa sodium hyaluronate are added, and water is added to 220 ml, mixed evenly, and sterilized by wet heat to obtain a cross-linked sodium hyaluronate gel composition (the theoretical molar cross-linking degree of the combination group is 7.5%).
[0085] Example 2
[0086] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 900 kDa, and 600 kDa was replaced by 300 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 300 kDa, and the remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%).
[0087] Example 3
[0088] Only the molecular weight of sodium hyaluronate of 1500 kDa in step (1) of Example 1 was replaced by 2800 kDa, and 600 kDa was replaced by 1000 kDa, and the molecular weight of sodium hyaluronate of 600 kDa in steps (2)-(3) was replaced by 1000 kDa, and the remaining steps were the same as Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%).
[0089] Example 4
[0090] Only the volume of 5 ml of sodium hydroxide in step (1) of Example 1 was replaced by 2 ml, and the volume of 1.5 ml of sodium hydroxide in step (2) was replaced by 0.6 ml, and the remaining steps were the same as in Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%).
[0091] Example 5
[0092] Only the amount of 1500 kDa sodium hyaluronate in step (1) of Example 1 was replaced by 1.8 g, and the amount of 600 kDa sodium hyaluronate was replaced by 0.2 g, and the remaining steps were the same as Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%).
[0093] Example 6
[0094] Only 100% of the cross-linked sodium hyaluronate II′ microparticles in step (2) of Example 1 were added to step (3) instead of 50%, and the remaining steps were the same as Example 1 (the theoretical molar cross-linking degree of the combination group was 7.1%).
[0095] Comparative Example 1
[0096] Only the step (1) in Example 1, "adding 5 ml of 250 mg / mL sodium hydroxide solution" was replaced by "adding 5 ml of 100 mg / mL sodium hydroxide solution", and the remaining steps were the same as Example 1 (the theoretical molar cross-linking degree of the combination group was 7.5%).
[0097] Comparative Example 2
[0098] Only the step (1) in Example 1, "take 1.5 g of 1500 kDa sodium hyaluronate raw material, take 0.5 g of 600 kDa sodium hyaluronate raw material" is replaced by "take 2 g of 1500 kDa sodium hyaluronate raw material", and the remaining steps are the same as Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%).
[0099] Comparative Example 3
[0100] Only the step (1) in Example 1, "take 1.5 g of 1500 kDa sodium hyaluronate raw material, take 0.5 g of 600 kDa sodium hyaluronate raw material" is replaced by "take 2 g of 600 kDa sodium hyaluronate raw material", and the remaining steps are the same as Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%).
[0101] Comparative Example 4
[0102] Only step (3) of Example 1 is replaced by: adding the micronized particles of cross-linked sodium hyaluronate II' of step (2) and 0.3 g of 600 kDa non-cross-linked sodium hyaluronate to cross-linked sodium hyaluronate I', mixing them evenly to obtain cross-linked sodium hyaluronate. The remaining steps are the same as those of Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%).
[0103] Comparative Example 5
[0104] Preparation of cross-linked sodium hyaluronate gel: Take 2.9 g of 1500 kDa sodium hyaluronate raw material, add 20 ml of water, add 12.5 ml of 20 mg / mL sodium hydroxide solution to dissolve, add 0.1 ml of BDDE solution, mix well, react at 25° C. for 30 h to obtain a cross-linked sodium hyaluronate gel. Then, the gel composition is prepared by the same operation as in step (4) of Example 1 (the theoretical molar cross-linking degree of the combination group is 7.5%).
[0105] Performance Testing
[0106] The gel samples of the embodiments and comparative examples were tested for performance, including elastic modulus, water absorption, crosslinking degree, appearance, and stress-strain scanning. The specific testing methods are as follows:
[0107] Elastic modulus: 2 g of gel sample was taken respectively, and the modulus of the gel sample before and after wet heat sterilization was tested using a rheometer (TA) at 25°C and a frequency of 1 Hz.
[0108] Water absorption: Take 1 g of gel sample, add 5 ml of water, seal, and let stand at room temperature for 1 hour. Carefully pour out the water on the top and record the mass of the gel after water absorption (in g). Water absorption = (mass of gel after water absorption - gel sampling amount) ÷ gel sampling amount × 100%.
[0109] Cross-linking degree: Take 8g of gel sample, add 200g of ethanol, stir and mix, and let stand to precipitate. Collect the precipitate, dry at 80℃, degrade it with 2ml of 0.5mol / L sulfuric acid solution at 100℃ until the solution is transparent, neutralize it with 1mol / L sodium hydroxide, and freeze-dry it. Deuterated DMSO is used as solvent, and hydrogen nuclear magnetic resonance is used to determine the molar cross-linking degree according to the area normalization method. Cross-linking degree = [δ = 1.5 peak area / 4] / [δ = 1.9 peak area / 3], where the peak at 1.5ppm represents the (-methene-) group of the BDDE molecule, and the peak at 1.9ppm represents the n-acetylglucosamine in the cross-linked sodium hyaluronate gel.
[0110] Appearance: Samples for water absorption test were taken separately, freeze-dried and observed using a scanning electron microscope.
[0111] Stress-strain scanning: 2 g of gel sample was taken and scanned by rheometer (TA) at 25° C., frequency 1 Hz, and deformation amount 0.05% to 1000%.
[0112] The characterization results are shown in Table 1 and Figure 1-3 shown.
[0113] Table 1
[0114]
[0115] It can be seen from the results in Table 1 that the samples of Examples 1-6 of the present invention have high water absorption and high crosslinking efficiency. The absorption rate of Example 1 can reach 200%, which is much higher than that of Comparative Examples 1-3. This is because in Example 1, high and low molecular weight HA are crosslinked in a large amount of alkaline solution and low molecular weight HA is crosslinked in a small amount of alkaline solution. The large amount of alkaline solution can fully destroy the hydrogen bonding between sodium hyaluronate, so that the high and low molecular weight HA molecular chains are fully extended and stretched, and the molecular chains of low molecular weight HA can freely perform irregular translation or rotation while stretching, and the high and low molecular weight sodium hyaluronates form interlaced crosslinks, so that the low molecular weight sodium hyaluronate Sodium hyaluronate can be interspersed or erected between high molecular weight sodium hyaluronate. At the same time, the amount of alkaline solution is large, which causes a certain degradation of the molecular weight of sodium hyaluronate, thereby cross-linking to form a loose structure with a large mesh spacing, thereby improving water absorption; while in comparative example 1, the amount of alkali is the same, and it is difficult to form a mutually interpenetrating chimeric structure. In comparative examples 2-3, since the molecular weight of the HA raw material is a single molecular weight during the first cross-linking, it is difficult to form a loose network structure, so the water absorption is relatively low; although a certain chimeric structure can be formed in comparative example 4, the water absorption effect is improved to a certain extent, but it does not make full use of the residual cross-linking agent, resulting in low cross-linking efficiency, and the water absorption effect is still limited. In comparative example 5, under conventional single molecular weight conditions, cross-linking mostly occurs between parallel chains, the cross-linked network is relatively dense, and the mesh spacing is small, resulting in poor water absorption.
[0116] It can also be seen from Table 1 that the elastic modulus of Examples 1-6 is relatively high, and the loss rate is within 15%, which is significantly better than the modulus loss rate of Comparative Examples 1-5. This indicates that through the process of the present invention, high and low molecular weight HA are formed into a loose network structure under the condition of a large amount of alkaline solution, and then under the condition of a small amount of alkaline solution, low molecular weight HA is used as a raw material. Due to the strong hydrogen bonding between HA, the molecular chain entanglement is relatively common, and it is easy to react quickly to form a compact network structure to obtain micron gel particles. By adding water to the first cross-linked product with a large amount of alkaline solution to adjust and dilute it, the condition of a large amount of alkaline solution is changed to a condition of a small amount of alkaline solution, and then the micron gel particles and HA are added to continue the reaction, so that the compact structure can penetrate into the looser structure to form a cross-linked HA gel with a soft elastic mosaic structure in which loose pores wrap elastic hard balls. The soft elastic mosaic structure formed improves the overall structural stability of the gel and can withstand wet heat sterilization. The loss rate of the elastic modulus after sterilization is relatively low. This can also be seen from the data of Example 1 and Comparative Example 4 that by diluting the first cross-linked product and then mixing it with the second cross-linked product, HA, the cross-linking efficiency can be significantly improved, and the water absorption of the gel composition can also be improved.
[0117] The water absorption effect of the gel composition samples is as follows Figure 1As shown in the figure, it can be seen that for gel samples of the same mass, after absorbing water and standing for 1 hour at room temperature, the volume of the samples of Examples 1, 3, and 5 after absorbing water and swelling reaches 2.5 to 3 times the volume before absorbing water, while the volume of the samples of Comparative Examples 1, 3, and 5 after absorbing water and swelling is 1.5 to 2.0 times the volume before absorbing water. This further illustrates that the mesh mosaic structure with larger pores formed by the gel composition in the embodiment can make the gel composition have better water absorption, and also have good ductility and water-locking and moisturizing effects, and is more suitable for flat injection filling of the inner and outer surfaces of the cavity.
[0118] The SEM image of the appearance of the gel composition sample is as follows: Figure 2 As shown, compared with Comparative Examples 1, 3, and 5, the pores of Examples 1, 3, and 5 are larger, indicating that the gel composition forms a mesh mosaic structure with larger pores. The presence of this structure can improve the water absorption of the sample; and by adjusting the ratio of high and low molecular weight HA, and the range of high and low molecular weight HA, the size of the pore structure can be flexibly controlled. In Comparative Example 1, the size of the pore structure formed is significantly smaller than that in Example 1. This is because the amount of alkaline solution is not controlled during the cross-linking process, making it difficult to form loose macropores. Comparative Example 5 also forms a relatively compact pore structure. This may be because under the conditions of conventional single molecular weight cross-linking, cross-linking mostly occurs between parallel chains, the cross-linked network is relatively dense, and the mesh spacing is small.
[0119] The stress-strain scanning curve of the gel composition sample is as follows: Figure 3 As shown in the figure, it can be seen that the linear viscoelastic zone of the gel composition of Example 1 is 0.05% to 40%, while the linear viscoelastic zone of the gel composition of Comparative Example 5 is 0.05% to 6%. Compared with Comparative Example 5, the linear viscoelastic zone of Example 1 is wider, indicating that the gel composition has stronger deformation resistance, weaker foreign body sensation, better consistency with tissue movement, and better compatibility with tissue.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cross-linked hyaluronic acid or a salt thereof, characterized in that: The preparation method of the cross-linked hyaluronic acid or its salt comprises the following steps: (1) mixing hyaluronic acid I or its salt, hyaluronic acid II or its salt, a first alkaline solution and a cross-linking agent, and reacting them to obtain a cross-linked hyaluronic acid I′ or its salt; (2) mixing hyaluronic acid III or its salt, a second alkaline solution and a cross-linking agent, and reacting them to obtain cross-linked hyaluronic acid II′ or its salt; (3) diluting the cross-linked hyaluronic acid I′ or its salt obtained in step (1) with water, adding the cross-linked hyaluronic acid II′ or its salt and hyaluronic acid IV or its salt obtained in step (2), mixing and reacting to obtain the cross-linked hyaluronic acid or its salt; The mass concentration of the first alkaline solution is higher than the mass concentration of the second alkaline solution; the molecular weight of the hyaluronic acid I is higher than the molecular weights of the hyaluronic acids II, III and IV.
2. The cross-linked hyaluronic acid or its salt according to claim 1, characterized in that The concentration of the first alkaline solution in step (1) is 10 to 100 mg / mL, preferably 12 to 90 mg / mL, and more preferably 15 to 80 mg / mL; the concentration of the second alkaline solution in step (2) is 0.1 to 50 mg / mL, preferably 1 to 40 mg / mL, and more preferably 5 to 30 mg / mL.
3. The cross-linked hyaluronic acid or its salt according to claim 1, characterized in that The molecular weight of the hyaluronic acid I is 900-3000 kDa, preferably 1000-2000 kDa, more preferably 1200-1600 kDa; the molecular weight of the hyaluronic acids II, III and IV is 100-1000 kDa, preferably 300-800 kDa, more preferably 400-700 kDa.
4. The cross-linked hyaluronic acid or a salt thereof according to any one of claims 1 to 3, characterized in that The mass ratio of hyaluronic acid I or its salt to hyaluronic acid II or its salt in step (1) is 2-10:1, preferably 3-9:
1.
5. The cross-linked hyaluronic acid or a salt thereof according to any one of claims 1 to 3, characterized in that: The ratio of the cross-linked hyaluronic acid I′ or its salt to the cross-linked hyaluronic acid II′ or its salt is 1-10:1, preferably 2-6:
1.
6. The cross-linked hyaluronic acid or a salt thereof according to any one of claims 1 to 3, characterized in that The amount of hyaluronic acid IV or its salt added is 5-30% of hyaluronic acid I or its salt relative to hyaluronic acid I or its salt.
7. The cross-linked hyaluronic acid or a salt thereof according to any one of claims 1 to 3, characterized in that The reaction temperature in steps (1), (2) and (3) is 20 to 30° C.; preferably, the reaction time in steps (1), (2) and (3) is 4 to 30 hours.
8. The cross-linked hyaluronic acid or a salt thereof according to any one of claims 1 to 3, characterized in that The hyaluronate is selected from any one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate, magnesium hyaluronate, ammonium hyaluronate, tetrabutylammonium hyaluronate, bismuth hyaluronate and zinc hyaluronate, preferably sodium hyaluronate; The cross-linked hyaluronate is selected from any one of cross-linked sodium hyaluronate, cross-linked potassium hyaluronate, cross-linked calcium hyaluronate, cross-linked magnesium hyaluronate, cross-linked ammonium hyaluronate, cross-linked tetrabutylammonium hyaluronate, cross-linked bismuth hyaluronate and zinc hyaluronate, preferably cross-linked sodium hyaluronate; preferably, the cross-linking degree of the obtained cross-linked hyaluronic acid or its salt is 1% to 6%, preferably 1.5% to 5%; Preferably, the alkaline solution is selected from: a solution prepared by one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium sulfite, and potassium sulfite, more preferably a sodium hydroxide solution; Preferably, the cross-linking agent is selected from: one or a combination of two or more of 1,4-butanediol diglycidyl ether, divinyl sulfone, polyethylene glycol, genipin and carbodiimide, more preferably 1,4-butanediol diglycidyl ether.
9. A cross-linked hyaluronic acid or salt composition, characterized in that: The composition comprises: the cross-linked hyaluronic acid or its salt as claimed in claim 1, non-cross-linked hyaluronic acid or its salt, phosphate buffer, local anesthetic and water-soluble cellulose.
10. The composition according to claim 9, characterized in that The mass concentration of the cross-linked hyaluronic acid or its salt in the composition is 1 to 30 mg / ml; Preferably, the water-soluble cellulose is selected from one or more of hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, hydroxybutyl methylcellulose, ethyl methylcellulose and carboxymethyl cellulose; Preferably, the water-soluble cellulose content ranges from 0.01 to 40 mg / ml; Preferably, the phosphate buffer comprises disodium hydrogen phosphate, sodium dihydrogen phosphate and potassium chloride; Preferably, the local anesthetic is selected from the group consisting of: amide type and ester type or a combination thereof.
11. A method for preparing the composition according to any one of claims 9 to 10, comprising the steps of: The cross-linked hyaluronic acid or its salt as described in claim 1 is taken out after dialysis, and the pH value of the system is first adjusted to 10-11 with a hydrochloric acid solution, and then the pH value of the system is adjusted to neutral with a lactic acid solution, and then a phosphate buffer, a local anesthetic, a water-soluble cellulose, and a non-cross-linked hyaluronic acid or its salt are added, mixed, and sterilized by wet heat to obtain a composition.
12. Use of the cross-linked hyaluronic acid or its salt according to claim 1, or the composition according to claim 10, or the composition prepared by the preparation method according to claim 11 in the preparation of medicines, tissue engineering materials, and cosmetics.
13. A use according to claim 12, characterized in that: The tissue engineering materials include soft tissue filling materials, cartilage repair materials, and tissue engineering scaffolds.
Citation Information
Cited By
Composition comprising microspheres and crosslinked hyaluronic acid or salt thereof, and preparation method therefor and use thereof
WO2026113956A1
